2002
DOI: 10.1038/sj.jhh.1001304
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic value of blood pressure in acute stroke

Abstract: Manipulation of blood pressure (BP) in acute stroke may improve outcome. Despite various studies, data on the prognostic significance of early BP in stroke remain unclear. Therefore, we studied the relationship between various BP variables in the acute phase of stroke and functional outcome at 3 months. Blood pressures were collected by reviewing BP records of 817 patients who were admitted to our stroke unit between 1987 and 1992. Besides the first systolic and diastolic admission BP (SBP and DBP), we also us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 31 publications
1
25
0
Order By: Relevance
“…415,421,422,424,428,429 Three studies found that decreases in blood pressure were associated with poor clinical outcomes. 415,421,428 Two studies found no association between blood pressure fluctuations and clinical outcomes. 424,429 One study found that decreases in blood pressure were associated with favorable clinical outcome.…”
Section: March 2013mentioning
confidence: 99%
“…415,421,422,424,428,429 Three studies found that decreases in blood pressure were associated with poor clinical outcomes. 415,421,428 Two studies found no association between blood pressure fluctuations and clinical outcomes. 424,429 One study found that decreases in blood pressure were associated with favorable clinical outcome.…”
Section: March 2013mentioning
confidence: 99%
“…13 The Registry started in 1988 and at the time of this study had data on 1843 patients. We explored the Registry and compared the prevalence of first-ever territorial cerebral infarcts and cardio-embolic stroke in both hemispheres.…”
Section: Study 2: Stroke Registrymentioning
confidence: 99%
“…In addition, we looked at side differences for small deep lacunar infarcts, because this type of infarct would not be expected to occur more frequently on one side. Definitions to classify stroke subtypes have been described before 13 and are based on the Trial of Org 10172 in Acute Stroke Treatment (TOAST) criteria. 17 Analyses were performed for the whole group of patients with first-ever stroke as well as for the subgroup of patients who were known to be hypertensive.…”
Section: Study 2: Stroke Registrymentioning
confidence: 99%
See 1 more Smart Citation
“…The ‘window’ size of 100 is considered to give robust estimates of probability of outcome of interest in that central interval of baseline BP from about 200 patients with and without thrombolysis. Boreas et al [16] have used a similar method to explore the cut-off point of BP, though baseline BP could not be identified as independent predictors of stroke outcome [16]. …”
Section: Discussionmentioning
confidence: 99%